Fluorinated Electrolytes for Li-S Battery: Suppressing the Self-Discharge with an Electrolyte Containing Fluoroether Solvent. Issue 1 (1st January 2015) - Azimi, Nasim; Xue, Zheng; Rago, Nancy Dietz; Takoudis, Christos; Gordin, Mikhail L.; Song, Jiangxuan; Wang, Donghai; Zhang, Zhengcheng
Abstract : The fluorinated electrolyte containing a fluoroether 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether (TTE) was investigated as a new electrolyte for lithium-sulfur (Li-S) batteries. The low solubility of lithium polysulfides (LiPS) in the fluorinated electrolyte reduced the parasitic reactions with Li anode and mitigated the self-discharge by limiting their diffusion from the cathode to the anode. The use of fluorinated ether as a co-solvent and LiNO3 as an additive in the electrolyte shows synergetic effect in suppressing the self-discharge of Li-S battery due to the formation of the solid electrolyte interphase (SEI) on both sulfur cathode and the lithium anode. The Li-S cell with the fluorinated electrolyte showed prolonged shelf life at fully charged state.